Prevalence and impact of respiratory symptoms in a population of patients with COPD in Latin America: The LASSYC observational study (2018)
Background To analyse the relationship between symptoms at different times during the 24-hour day and outcomes in COPD. Methods Observational cross-sectional study in a patients from 7 Latin American countries. The frequency of symptoms in the morning, at night and during the day was explored by means of standardised and validated questionnaires, and the relationship between symptoms and exacerbations and quality of life were investigated. Results 734 patients (59.6% male, mean age 69.5 years, mean FEV1 50% predicted normal) were recruited. The most frequent symptoms during the day were dyspnea (75% of patients, of which 94% mild-moderate) and cough (72.2%, of which 93.4% mild-moderate). Highly symptomatic patients had a greater impairment in FEV1, more exacerbations and worse scores in COPD assessment test (CAT) and Body Mass Index, Obstruction, Dyspnoea and Exacerbations (BODEx) index (all p and lt; 0.001). Morning symptoms were more frequent than night-time symptoms, particularly cough and dyspnoea (morning: 50.1% and 45.7%; night-time: 33.2% and 24.4%, respectively), and mostly rated as mild or moderate. Patients with morning or night-time symptoms presented with worse severity of daytime symptoms. There was a strong correlation between intensity of daytime with morning or night-time symptoms, as well as with CAT score (r = 0.715; p and lt; 0.001), but a weak correlation with FEV1 (r = ?0.205; p and lt; 0.001). Conclusion Morning symptoms were more frequent than night-time symptoms, and having either morning and/or night-time symptoms was associated with worse severity of daytime symptoms. Increased symptoms were strongly associated with worse quality of life and more frequent exacerbations, but weakly associated with airflow limitation. Clinical trial registration NCT02789540. © 2017 Elsevier Ltd